THE NURUL KALAM GREAT MOSQUE IN PEMALANG REGENCY - FATUROKHIM (NIM : 15214058), AMIR
The Nurul Kalam Great Mosque is located in Pemalang District, Pemalang Regency, north coast of Central Java Province. The mosque has inadequate capacity and facilities as a great mosque, therefore the effort of redesigning the Great Mosque of Nurul Kalam with a wider land, in order to meet the criteria and capacity required in the Mosque Management Development Standards, Ministry of Religious Affairs of the Republic of Indonesia. The new Nurul Kalam Great Mosque is built on 2.5 ha of land, with a capacity of 8000 pilgrims, and completeness of facilities in accordance with the criteria for designing the great mosque. The facilities accommodate various activities such as social activities, education, services, sports, and tourism. The design concepts developed from the analysis and design issues include: first, the garden concept inspired by the potential of land passed by the river, the analogy of the garden of heaven. Second is the concept of the ship of the ummah applied to the mass form of the mosque building, the analogy of the ship that becomes the vehicle to go to heaven. The form of the ship was also adopted from the local cultural heritage of the Pemalang people who were living as fishermen. The redesign project of Nurul Kalam Great Mosque is expected to be a tourist attraction for the people, and can improve the image of Pemalang Regency.